Old Testament History and Archaeology - Miller, James Maxwell (The Biblical archaeologist, 1987)
Nonwritten, artifactual evidence is silent by nature and not particularly useful for dealing with specific historical facts. Yet the artifactual record does occasionally speak with a distinctive voice that biblical historians should be prepared to hear.